Effect of Fusarium Head Blight Management Practices on Mycotoxin Contamination of Wheat Straw - Bissonnette, Kaitlyn M (Plant disease, 2018)
Management of Fusarium graminearum-associated mycotoxins in wheat grain has been extensively evaluated, but little is known about management of mycotoxins in straw. Two research trials were conducted at four locations from 2011 to 2014. The objective of the first trial was to determine the efficacy of fungicides, and the objective of the second trial was to evaluate the use of integrated disease management strategies, for the control of Fusarium head blight (FHB) and reducing the concentration of the Fusarium mycotoxins deoxynivalenol, 3-acetyl-deoxynivalenol, and 15-acetyl-deoxynivalenol in straw. In the first trial, it was determined that demethylation inhibitor (DMI) fungicides did not offer significant (P ≤ 0.05) reductions of mycotoxin concentrations in the straw compared with a no-fungicide control treatment, but significant (P ≤ 0.05) reductions in mycotoxin concentration were observed in the control when compared with treatments with the application of quinone outside inhibitor (QoI)-containing fungicides. In the second trial, mycotoxin concentrations in the straw were significantly (P ≤ 0.05) reduced in the moderately resistant cultivar compared with the susceptible cultivar, but were not affected by the use of a fungicide. The practices typically used to manage Fusarium mycotoxins in wheat grain, especially the selection of resistant cultivars and not using a QoI fungicide, may be an effective means to reduce mycotoxin concentrations in the straw